Mechanism regulating reactive oxygen species in tumor induced myeloid-derived suppressor cells: MDSC and ROS in cancer - Corzo, Cesar A. (2009)
Myeloid-derived suppressor cells (MDSC) are a major component of the immune suppressive network described in cancer and many other pathological conditions. Recent studies have demonstrated that one of the major mechanisms of MDSC-induced immune suppression is mediated by reactive oxygen species (ROS). However, the mechanism of this phenomenon remained unknown. In this study we observed a substantial up-regulation of ROS by MDSC in all of seven different tumor models and in patients with head and neck cancer. The increased ROS production by MDSC is mediated by up-regulated activity of NADPH oxidase (NOX2). MDSC from tumor-bearing mice had significantly higher expression of NOX2 subunits, primarily p47(phox) and gp91(phox), compared to immature myeloid cells from tumor-free mice. Expression of NOX2 subunits in MDSC was controlled by the STAT3 transcription factor. In the absence of NOX2 activity, MDSC lost the ability to suppress T-cell responses and quickly differentiated into mature macrophages and dendritic cells. These findings expand our fundamental understanding of the biology of MDSC and may also open new opportunities for therapeutic regulation of these cells in cancer.